Residue and microwear analyses of the stone artifacts from Schöningen. Issue 89 (December 2015) - Rots, Veerle; Hardy, Bruce L.; Serangeli, Jordi; Conard, Nicholas J.
Abstract: Stone artifacts from Schöningen 12 and 13 were examined microscopically to identify residues, wear, and manufacturing traces in order to clarify their possible anthropogenic origins and their function. We present evidence showing that the stone tools were used for working wood and hide and for cutting meat. The results from the use-wear and residue analyses proved complementary in several instances. Suggestive evidence of hafting was observed on a few pieces, which is particularly interesting given the identification of wooden hafts at the site. The positive results of this analysis demonstrate the efficacy and potential of these techniques for Lower Paleolithic sites such as Schöningen.